OPTIMALISASI PENGADAAN BAHAN BAKU DALAM RANGKA MEMINIMALKAN TOTAL BIAYA PERSEDIAAN TEMBAKAU PADA PT BENTOEL INTERNATIONAL INVESTAMA DI MALANG - Dwi Dayanti Oktavia; Peni Indarwati; Marhaerni Fikky Febriananta (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2019)
A company should maintain an adequate or optimal level of inventory so that production operations can run smoothly and efficiently. What needs to be considered in this case is that the required raw materials are always available, so as to guarantee the smooth production process. However, the amount of inventory should not be too much because this will harm the company. Too much inventory will increase maintenance costs and storage costs in the warehouse. In addition, the amount of inventory that is too much can also increase the likelihood of losses due to damage and loss of quality that can reduce company profits. And vice versa, the amount of inventory that is too small will hamper the production process so that the company will suffer a lot of losses including: the machine does not work as it should, many workers are unemployed, and can even result in the cessation of the production process. This study aims to determine how the calculation of raw materials, what is the total cost of raw material inventory if the company establishes an EOQ (Economic Order Quantity) policy, what is the limit or point of ordering raw materials needed by the company during the grace period at PT.Bentoel International Investama in Malang.The population used is the supply of tobacco raw materials at PT. Bentoel International Investama, where this research was conducted by interview and documentation. The variable in this study is the supply of raw materials. The analysis used is the EOQ (Economic Order Quantity) method.The results of the study, if using the EOQ method in 2017 the cost savings of Rp 40,290,256,931, while in 2018 the cost savings of Rp. 44,388,428,549. Thus there is a difference between inventory policies carried out according to the company with EOQ calculations. It can be concluded that the supply of raw materials every year has increased raw materials, the frequency of purchasing raw materials when using raw materials when using the EOQ method is 2 times in one period, the limit for ordering raw materials needed by companies when using the 2017 EOQ method is 218,176.7 kg, while in 2018 it will be 210,853 kg. The total cost of raw material inventory calculated according to EOQ is less than that spent by the company, so there is a cost savings of raw material inventory